BOOK REVIEW Bradshaw, M; George W. White, Joseph, P. Dymond; and Elizabeth Chacko (2007). Contemporary World Regional Geography: Global Connections; Local Voices. McGraw Hill Higher Education Boston 2nd Edition, Hard Cover Price: Not Stated. - M.O. LAWAL (Faculty of Geography, Universitas Gadjah Mada, 2012)
.